New palynological data for Toarcian (Lower Jurassic) deep-marine sandstones of the Western Caucasus, southwestern Russia - Goryacheva, Anna A.; Zorina, Svetlana O.; Ruban, Dmitry A.; Eskin, Alexei A.; Nikashin, Konstantin I.; Galiullin, Bulat M.; Morozov, Vladimir P.; Mikhailenko, Anna V.; Nazarenko, Olesya V.; Zayats, Pavel P. (Geologos, 2018)
Information on Jurassic palynomorphs from the Greater Caucasus is potentially of great importance, but its availability to the international research community is severely limited. New palynological data for Toarcian deposits of the Western Caucasus are recorded in the present paper. Particularly, dinoflagellate cysts are described for the first time from the Bagovskaja Formation; palynomorphs are found in sandstone levels within this unit. The most representative assemblage includes pollen (with predominant bisaccate pollen), spores (Cyathidites being commonest), and dinoflagellate cysts amongst which the predominant taxon is Nannoceratopsis spiculata. The dinocyst assemblage implies a late Toarcian age for the upper part of the Bagovskaja Formation. On the basis of these new palynostratigraphical results, the range of the formation is extended; previously, only the lower part had been dated on ammonite evidence.